Buffer capacity of solutions for estimating soil acidity - Catani, R. A.; Jacintho, A. O.; Pizzinatto, A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1972)
Buffer capacity or index was determined for SMP, - Woodruff, Woodruff (1 + 1), (1+2) and (1 + 3), 1,00 N, 0,50 N and 0,25 N calcium acetate solutions. The data obtained showed that SMP solution presented a constant value for buffer capacity when 0.10 - 0.15 - 0.20 - 0.25 - 0.30 - 0.35 - 0.40 - 0.45 and 0.50 milliequivalents of HCl pointing out that the pH of all solutions decreased linearly water. The equations were calculated by the method or least squares for the relationship between buffer solution pH and added amount of HCl pointing out that the pH of all solutions decrease linearly with respect to the quantity of HCl added.